EFFECT OF THE Uncaria tomentosa LEAVES HYDROALCOHOLIC EXTRACT ON PHYSIOLOGICAL PARAMETERS AND PERFORMANCE INDICES OF BROILER CHICKENS - LOAYZA-BESARES, Jairo (2024)
The continuous use of antibiotics as growth promoters in poultry has caused bacterial resistance and public health risk. The aim of this study was to determine the effect of hydroalcoholic extract from Uncaria tomentosa (HAEUt) leaves on physiological parameters and performance indices of broiler chickens. One hundred COBB 500 chickens of 1 day old and 42.22 g weight were used. The HAEUt was supplemented in drinking water at 0, 1.34, 2.68 and 4.03 mg/mL and from 1 to 42 days. The hematocrit, hemoglobin, total protein, albumin, alanine aminotransferase (ALT), aspartate aminotransferase (AST), daily feed intake (DFI), daily weight gain (DWG), and the feed conversion rate (FCR), at 42 days old was determined. A complete randomized design (CRD) with a factorial arrangement was used. Hematocrit, hemoglobin and albumin increased as theHAEUt increased (p<0.05); at the same time, DFI decreased with the increase in the HAEUt (p<0.05), while the DWG and the FCR did not vary (p>0.05). Conclusively, the HAEUt improved the performance of the broiler chickens, because the HAEUt would modulate anorexigenic hypothalamic neuropeptides which might be responsible for DFI reduction and maintaining DWG and FCR ofchickens and it would improve farmers’ incomes.